Love-Death Hanna Schmitz in Bernhard Schlink's The Reader Novel (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Literary research, essentially is a process of meeting between literary works and researchers. In this case, it is necessary to pay attention to the reader's situation and reading situation when dealing with literary works. The reader already has a certain amount of knowledge that is realized or will not equip the reading. The knowledge will fill the horizon of understanding when reading the text (novel) with its contextuality. That horizon then directs the reading. Therefore, reading is not a process that runs in one direction, but rather a form of dynamic interaction between the text and the reader. Likewise in the novel The Reader by Bernhard Schlink, readers / researchers will not be able to be separated from the context behind the work. The history of the holocaust sets the stage for telling love stories between Hanna and Michael. The history and love story are interrelated. Literary writers provide a strong setting in the narrative of telling the novel. In the end, the novel became a documentary of the imagination and creativity of the writer in relation to social relations.